The Routledge History of Fashion and Dress, 1800 to the Present - Pouillard, Veronique; Dubé-Senécal, Vincent (Routledge Histories, 2024)
The time span covered by The Routledge History of Fashion and Dress starts in the nineteenth century, with the aftermath of the consumers' revolution, and reaches all the way to the present. The fashion and garment industries have been international from the beginning and, as such, this volume looks at the history of fashion and dress through the lenses of both international and global history. Because fashion is also a multifaceted subject with humanagency at its core, at the confluence of thematerial (fabrics, clothing, dyes, tools, and machines) and the immaterial (savoir-faire, identities, images, and brands), this volume adopts a transdisciplinary perspective, opening its pages to researchers from a variety of complementary fields. The chapters in this volume are organized based on their relationship to five fields of study: economics and commerce, politics, business, identities, and historical sources. Paying particular attention to change, the book goes beyond the great fashion capitals and well-known fashion centers and points to the broader geographies of fashion. Particular geographical areas focus on the emergence of new fashion systems and business models, whether they be in Sweden, Bangladesh, or Spain, or on the African continent, considered to be the "new frontier" of the industry. Covering myriad aspects of the subject this is the perfect companion for all those interested in history of dress and fashion in the modern world.